Uništenje Univerzitetske biblioteke u Luvenu u Prvom svetskom ratu i njena obnova u posleratnom period = Destructon of the University of Leuven Library in First World War and its Renovation in the Post-War Period - Vesna Živković (The National and University Library of Bosnia and Herzegovina, 2021)
Uništavanje biblioteka i njenih kolekcija od davnina su sastavni deo ratova i osvajačkih pohoda: od uništenja Aleksandrijske biblioteke u starom veku, jezuitskih biblioteka u Kini tokom 17. i 18. veka, Narodne biblioteke u Beogradu u Drugom svetskom ratu, Nacionalne i univerzitetske biblioteke Bosne i Hercegovine u Sarajevu 1992. godine, pa sve do spaljivanja rukopisa u biblioteci u Timbuktuu 2013. godine. U fokusu ovog rada je uništenje Univerzitetske biblioteke u Luvenu, od strane nemačke okupacione vojske u Prvom svetskom ratu, kao i njena obnova u posleratnom periodu. = The destruction of libraries and its collections has long been an integral part of wars and conquests: from the destruction of the Library of Alexandria in the old century, Jesuit libraries in China during the 17th and 18th centuries, the National Library in Belgrade in World War II, the National and University Library of Bosnia and Herzegovina in Sarajevo in 1992, until the manuscript was burned in the library in Timbuktu in 2013. The focus of this paper is the destruction of the University Library in Leuven by the German occupation army in First World War, as well as its restoration in the post-war period.